Preventing young farmers from leaving the farm: Investigating the effectiveness of the young farmer payment using a behavioural approach. (March 2019) - May, Daniel; Arancibia, Sara; Behrendt, Karl; Adams, John
Abstract: The number of young farmers has decreased over recent decades in several developed countries such as the United States and European countries. A recent strategy adopted by the European Union to address the resulting age imbalance is the Young Farmer Payment which provides an additional payment on top of the average basic payment introduced in the last Common Agricultural Policy reform. The objective of this study is to determine, by means of a behavioural approach, how this payment influenced the incentives of young farmers to stay in the farm. Using the endogenous succession cycle model and the structural modelling technique, we found that the payment affected young farmers' willingness to stay through its influence on non-economic motivational goals. However, we also found that there are other factors that can be even more influential, such as pessimism about farming, community and family integration, participation in decision making, and the opinion of neighbours, among others. Based on the results, we argue that similar policies could be adopted in other countries, although policies would be more effective in addressing age imbalances if they are accompanied with complementary strategies aimed to deal with the identified social and psychological considerations.